VD_FINDINFO AI 227/11 - 35/2012 vom 29. Dezember 2011 - VD Tribunal cantonal (2011)
AIASSURANCE, RENTEEN GÉNÉRAL, DÉCISION DE RENVOI, MESURE D'INSTRUCTIONASSURANCE SOCIALE | 28 LAI, 4 LAI, 43 LPGA, 7 LPGA, 8 LPGA, 69 al. 2 RAI